Peculiarities of Posthypertonic Lysis in Erythrocytes of Several Mammals - Semionova, Elena A.; Yershova, Nataliya A.; Yershov, Sergey S.; Orlova, Nataliya V.; Shpakova, Nataliya M. (Problems of Cryobiology and Cryomedicine, 2016)
The erythrocyte sensitivity of some mammalian species (human, rat, rabbit) to posthypertonic lysis effect when varying NaCl concentration in dehydration medium, cell incubation duration and temperature was studied. We demonstrated here a determining role of dehydration stage (compared to rehydration one) for posthypertonic lysis development in mammalian erythrocytes, since the salt concentration in hypertonic medium and incubation duration in it determined the level of cell hemolysis. The loss of potassium cations by human and rabbit cells, depending on salt concentration in the medium was revealed at dehydration stage. The level of posthypertonic lysis in human, rat and rabbit erythrocytes was established as determined by experimental temperature conditions. Values of posthypertonic lysis of mammalian erythrocytes are lower at0Â°C, than at37Â°C, and this feature is much pronounced for animal cells. The results of comparative analysis of cell response to posthypertonic lysis effect showed rabbit erythrocytes to have the maximum resistance, and the minimum one was in rat cells. Probl Cryobiol Cryomed 2016; 26(1):73-83.